Az orvos gyógyító tevékenységének büntetőjogi vonatkozásai - Juhász, György (Debreceni Jogi Műhely, 2017)
The article introduces the criminal liability of the medical doctors in a nutshell. The topicality of this theme is exemplified by the increasing number of criminal procedures against physicians as trends show. During the introduction of the criminal liability of the medical practitioners, the article considers drawing a line between the liability of civil and criminal law of importance. After describing the matters concerning the drawing of line, the study is going to elaborate the legal brief of endangerment committed in the line of duty, followed by a review connecting the prior and the medical profession, presenting some legal cases, respectively. It is very essential to explore the legal brief of prohibited abortion and charlatanry, in addition to delineating the concepts of active and passive euthanasia, and, after having explained the refusal of provisions, it is necessary to aspire to draw a line between the prior mentioned and the legal brief of the assistance in suicide.